2020
DOI: 10.5937/tehnika2003297s
|View full text |Cite
|
Sign up to set email alerts
|

The content of copper and heavy metals in the multilayer soil mud from the Buchim lake under the Buchim mine's waste dump, Republic North Macedonia

Abstract: The intense mineral extraction in mining areas during the last several decades has produced a large amount of waste material and tailings, which release toxic elements to the environment. The aim of the study was to determine in two vertical profiles/sections (1 and 2) the heavy metal contents of samples derived from six samples, three from each section located in the porphyry copper mine Buchim area, Republic North Macedonia. The results have been compared to new Dutchlist (DL) and Kabata-Pendias (KP) standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Comparison of obtained data with reference data (Palache et al, 1944;Okrusch and Matthes, 2005), in average has shown only part of percent discrepancies between the values. Admixtures present within the pyrite composition strongly reflect the adjacent rock and mineralization setting of the Bučim deposit (Serafimovski 1992; Serafimovski et al, 2020;2021c).…”
Section: Ore Microscopy and Scanning Electron Microscopy Resultsmentioning
confidence: 99%
“…Comparison of obtained data with reference data (Palache et al, 1944;Okrusch and Matthes, 2005), in average has shown only part of percent discrepancies between the values. Admixtures present within the pyrite composition strongly reflect the adjacent rock and mineralization setting of the Bučim deposit (Serafimovski 1992; Serafimovski et al, 2020;2021c).…”
Section: Ore Microscopy and Scanning Electron Microscopy Resultsmentioning
confidence: 99%